Evaluating the My Life self-determination model for older youth in foster care: Establishing efficacy and exploring moderation of response to intervention. (December 2020) - Blakeslee, Jennifer E.; Powers, Laurie E.; Geenen, Sarah; Schmidt, Jessica; Nelson, May; Fullerton, Ann; George, Kevin; McHugh, Elizabeth; Bryant, Mary; ,
Abstract: Limited rigorous research has been conducted to evaluate the impact of interventions designed to promote the successful transitions of young people exiting foster care. The current study builds on previous experimental evaluations of the My Life Model (MLM) for self-determination enhancement, which demonstrated effectiveness in improving educational and transition-to-adulthood outcomes for youth in foster care with disabilities, including those with mental health challenges. The model features one-on-one youth-directed coaching and near-peer mentoring to increase self-determination and goal achievement. The current study was the first to test the impact of the model with a diverse population-based cohort of youth aged 16.5-18.5 in foster care (N = 293), including those with and without disabilities, on key model outcome indicators of self-determination and self-efficacy. This study also explored potential moderation by disability status, trauma symptoms, placement stability, and placement restrictiveness. Findings show that, compared to the randomized control group, the treatment group had greater post-intervention and one-year follow-up gains on several indicators of self-determination. Moderation analysis demonstrated no difference in intervention effectiveness for youth with or without disabilities, suggesting the universality of this approach. Findings also suggest that foster youth participants with low-to-average risks in terms of placement stability, placement restrictiveness, and traumatic stress levels seem to benefit most from the intervention, although youth who are at higher risk due to placement instability, high placement restriction, and high traumatic stress still showed some benefit of participating in the intervention on some measures. My Life is one of only a few intervention models with experimental evidence of effectiveness with older youth in foster care. This validation study establishes that the approach has benefits for both youth with and without disabilities and provides the first information available on the influence of critical barriers facing many youth in care.